The Esophageal Cancer - MUHIELDEEN, SAMIR (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Squamous carcinoma accounts for majority of esophaged cancinoma Most patients with esophaged cancer are middle aged or elderly with make to female ratio 2.5:1.Aim of study : to present a fairly representative picture of the carcinoma of esophagus in' yemen.Patients& Methods: Seventy-six patients were treated for carcinoma of esophagus over a 5 - year period by cardiothoracic and vascular surgeon working in Sana a - Yemen. Amongst them there were thirty one men and forty-five women, with male/female ratio 1:1.45, age incidence (range 38 - 40year).Results:. Adenocarcinoma was 65% of cases and other 35% was squamous cel! carcinoma. The major risk factors were founded chewing quat, silicon particles, thermal injury, diet deficient in vitamin, tannic acid (strong tea and sorghum wheat).The mortality rate was more than 15%, 9% females and 6% mates.Conclution: this study showes that acceptable early results for the treatment of esophaged cancer, can be obtained by a surgeon working in hospital with relatively basic facility . the cancer services may well improve long - term outcomes by facilitating both the deliver of multimodality conbined treatment